The Historical Problem and Solution of Forest Right in Uninhabited Islands - Miao YU; Yonghua TAN; Degang WANG; Wei MO (Haiyang Kaifa yu guanli, 2023)
The promulgation of the "Island Protection Law of the People's Republic of China" marks that the island management work of China has officially entered the stage of legalization and standardization. However, the proper handling of the historical problem left over before the law is an important issue in front of island management in China, among which the handling of the problems left over by the history of forest right in uninhabited islands is the key and difficult point. The difficulties in solving the forest rights of uninhabited islands are as follows: first, the legal basis for solving the forest rights of uninhabited islands is insufficient; Second, the contradiction between state ownership of uninhabited islands and collective ownership of forest right on uninhabited islands, and the overlapping contradiction between the collective ownership of forest right on uninhabited islands and the right to use the island; Third, the uninhabited islands into forest land use control. By analyzing and summarizing the experience of local management departments in dealing with the forest right of uninhabited islands, it is found that there are still many problems: the legal basis of collective forest land expropriation by the government is insufficient, the cost of forest land compensation is high, unclear registration of real estate right type, the change of land use type is not suitable for uninhabited islands, and the forest right have a great influence on the island project, etc. Aiming at the above problems, the management system of uninhabited islands in China is expected to be improved by constructing the treatment path of forest right problem of uninhabited islands. From the legal level, according to the particularity of uninhabited islands, revise and improve laws and regulations; From the management level, the pre-examination system of forest land occupied by development and utilization projects of uninhabited islands and the collection system of collective forest land of uninhabited islands should be established, and reasonable compensation standards and methods should be determined, and the right to use forest land of uninhabited islands should be treated according to the right to use land of uninhabited islands, to strengthen the supervision of the whole process of uninhabited island development and utilization projects, build the database and management information system of uninhabited island forest resources. From the technical level, the background investigation of uninhabited islands should be done well. The ecological suitability evaluation of uninhabited islands should be carried out in the single island planning. The ecological suitability evaluation of uninhabited islands should be carried out in the single island planning. The research on the dominant uses and types of islands used by projects of uninhabited islands should be strengthened.